Pressure-sensitive adhesive
Patent Information
- Application Number
- CN202580023730.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-04-03
- Filing Date
- 2025-04-02
- Publication Date
- 2026-10-27
Smart Images

Figure SMS_7 
Figure SMS_8 
Figure SMS_10
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of pressure-sensitive adhesives, which are commonly used for temporary or permanent connections of joined components. More specifically, this invention proposes a pressure-sensitive adhesive based on a polyacrylate copolymer of a specific composition, which achieves good adhesion as well as good shear life and peel adhesion, particularly on polar adhesive substrates, wherein a large proportion of the polyacrylate copolymer is based on renewable raw materials. Background Technology
[0002] In recent years, the quality requirements for pressure-sensitive adhesives have increased dramatically. One example is their use in electronic products such as smartphones and tablets. Here, adhesives must possess significant adhesive performance characteristics, such as high impact resistance, but also be compatible with typically highly sensitive electronic components. Ecological and social standards are also receiving increasing attention, such as the sourcing of raw materials. In this regard, there is a particular need for raw materials that are partially or even entirely derived from biological sources. This is part of the currently prevalent trend towards sustainable products, and is especially relevant to limited oil reserves and the resulting environmentally conscious requirements; adhesive manufacturers' customers are increasingly demanding products that meet these requirements.
[0003] In the aforementioned respects, poly(meth)acrylate has repeatedly proven to be a readily available starting material. Therefore, suitable formulations for poly(meth)acrylate-based pressure-sensitive adhesives have been continuously investigated.
[0004] For example, EP 2 062 955 A1 describes an aqueous pressure-sensitive adhesive composition that is essentially based on an acrylate polymer dispersed in water.
[0005] For plant-based acrylate pressure-sensitive adhesives, a typical example is an adhesive composition based on a copolymer comprising 90 to 99.5% by weight of 2-octyl (meth)acrylate, 0.5 to 10% by weight of (meth)acrylic acid, and less than 10% by weight of the reaction product of other monomers, as described in WO 2008 / 046000 A1.
[0006] EP 3 013 767 A1 discloses the use of a polymer obtained by polymerizing 2-octyl acrylate from a renewable source and optionally at least one other monomer as a binder for manufacturing coating compositions, wherein the polymer has a glass transition temperature of -30°C to 30°C.
[0007] EP 2 626 397 A1 discloses a pressure-sensitive adhesive comprising an acrylate-based polymer component, wherein at least 50% by weight of the monomers used to manufacture the polymer component are derived entirely from renewable raw materials.
[0008] EP 4 196 509 A1 discloses a pressure-sensitive adhesive comprising at least one copolymer traceable to a monomer composition comprising 45-75% by weight of at least one monomer selected from isoamyl acrylate, n-heptyl acrylate and 2-octyl acrylate, 24-50% by weight of at least one (meth)acrylate alkyl ester having an alcohol component having 1 to 4 carbon atoms, and 0.5 to 10% by weight of acrylic acid; and at least one adhesive strength-enhancing resin. Summary of the Invention
[0009] The purpose of this invention is to provide a pressure-sensitive adhesive, which has good adhesion, good shear life and peel adhesion, particularly on polar adhesive substrates, and can be manufactured from bio-based raw materials in a large proportion.
[0010] The first and general subject of the present invention for achieving the stated objective is a pressure-sensitive adhesive, comprising...
[0011] - At least one copolymer A, which is traceable to a monomer comprising or consisting of:
[0012] a) Isoamyl acrylate, greater than 75% to 98% by weight.
[0013] b) 0.5 to 15% by weight of acrylic acid; and optionally
[0014] c) 0 to 24.5% by weight of one or more other monomers;
[0015] as well as
[0016] - One or more cross-linking agents.
[0017] Optionally, the pressure-sensitive adhesive includes an adhesive-enhancing resin.
[0018] This pressure-sensitive adhesive has good adhesive properties that meet the above objectives, wherein not only the (co)polymer component but also the optional resin portion can be formulated largely based on renewable raw materials.
[0019] According to the present invention, as generally understood, "pressure-sensitive adhesive" or "pressure-sensitive adhesive substance" should be understood to mean a substance that is permanently tacky and has adhesive properties at least at room temperature. A pressure-sensitive adhesive is characterized in that it can be applied to a substrate and remain adhered thereto, wherein the pressure to be applied and the duration of such pressure are not specified in more detail. Generally, but in principle, depending on the exact type of pressure-sensitive adhesive, as well as the substrate, temperature, and air humidity, a short-term minimum pressure application of no more than brief, slight contact is sufficient to achieve an adhesive effect; in other cases, a higher pressure and a longer application time may be required.
[0020] Pressure-sensitive adhesives possess unique and characteristic viscoelastic properties that produce permanent tack and adhesive strength. They are characterized by the simultaneous occurrence of a viscous flow process and an elastic restoring force upon mechanical deformation. These two processes are specifically related in proportion to each other, depending not only on the exact composition, structure, and degree of crosslinking of the pressure-sensitive adhesive, but also on the rate and duration of deformation and the temperature.
[0021] A certain proportion of viscous flow is necessary for adhesion. Only the viscous portion—usually generated by macromolecules with relatively high mobility—can achieve good wetting and spreading of the substrate to be bonded. A high proportion of viscous flow results in high pressure-sensitive adhesive tack (also known as tack or surface adhesiveness), and therefore usually also high adhesion. Highly cross-linked systems, crystalline or glassy cured polymers, due to the lack of flowable portions, typically have little or no pressure-sensitive adhesive tack.
[0022] A certain proportion of elastic restoring force is necessary to achieve cohesion. This is generated, for example, by macromolecules with very long and highly entangled chains and physical or chemical cross-linking, and is capable of transmitting forces acting on the adhesive bond. This allows the adhesive bond to withstand sustained loads, such as sustained shear loads, for a sufficiently long time.
[0023] To more accurately describe and quantify the degree of elasticity and viscous components, as well as the proportions of each component to the others, the storage modulus (G′) and loss modulus (G″), which can be measured by dynamic mechanical analysis (DMA), are used. G′ is a measure of the elastic component of the material, and G″ is a measure of the viscous component. Both parameters depend on the deformation frequency and temperature.
[0024] These parameters can be determined using a rheometer. For example, the material under study is exposed to sinusoidal oscillating shear stress in a plate-to-plate arrangement. For shear stress-controlled instruments, the deformation as a function of time and the time shift of this deformation relative to the applied shear stress are measured. This time shift is called the phase angle δ.
[0025] The energy storage modulus G′ is defined as follows: G′ = (τ / γ) cos(δ) (τ = shear stress, γ = deformation, δ = phase angle = phase shift between the shear stress vector and the deformation vector). The loss modulus G″ is defined as follows: G″ = (τ / γ) sin(δ) (τ = shear stress, γ = deformation, δ = phase angle = phase shift between the shear stress vector and the deformation vector).
[0026] Specifically, a substance is considered a pressure-sensitive adhesive under the following conditions, and is specifically defined as a pressure-sensitive adhesive for the purposes of this invention: at 23°C, 10 0 In the deformation frequency range up to 10¹ rad / sec, both G′ and G″ are at least partially located between 10³ and 10. 7 The range of Pa. "Partially" means that at least a segment of the G′ curve lies within the range of 10. 0 The range of deformable frequencies up to and including 10¹ rad / sec (x-axis) and the range including 10³ to including 10 7 The window spanned by the range of G′ values of Pa (vertical axis) and at least one segment of the G″ curve also lies within the corresponding window.
[0027] The pressure-sensitive adhesive according to the present invention comprises at least one copolymer A, traceable to a monomer composition comprising or consisting of the following:
[0028] a) Isoamyl acrylate, greater than 75% to 99.5% by weight,
[0029] b) 0.5 to 15% by weight of acrylic acid; and optionally
[0030] c) 0 to 24.5% by weight of one or more other monomers;
[0031] The other monomer c) is different from monomers a) and b).
[0032] In particular, the monomers listed in a) can all be manufactured from renewable raw materials.
[0033] According to this disclosure, bio-based materials are materials manufactured based on renewable raw materials.
[0034] A method for producing bio-based acrylic acid (which can be used as monomer b) and as an acid component for monomers a) and c) uses glycerol as a starting material, which is produced in large quantities, for example, during the transesterification of vegetable oils with methanol to produce biodiesel and is therefore available. The method involves dehydrating the glycerol to acrolein; subsequently oxidizing the acrolein to acrylic acid in a single- or two-stage process. This method is described, for example, in US 2007 / 0129570 A1.
[0035] Another approach to manufacturing acrylic acid with a certain bio-based content is to use a (bio) mass balance scheme.
[0036] WO 2006 / 092272 A2 discloses a similar method in which glycerol is first converted into a dehydrated product containing acrolein, and then the dehydrated product is subjected to gas-phase oxidation to produce a product containing acrylic acid. Acrylic acid is obtained by contacting the oxidation product with a quenching agent and treating the quenched phase. This method enables the production of acrylic acid from renewable raw materials without the use of reactive compounds. Glycerol is preferably obtained from the saponification of animal or vegetable fats.
[0037] Bio-based acrylic acid can also be obtained by generating lactic acid (2-hydroxypropionic acid) or 3-hydroxypropionic acid as a fluid—particularly in an aqueous phase—from biological materials, dehydrating the hydroxypropionic acid to obtain an acrylic acid-containing fluid, and purifying the acrylic acid-containing fluid. The desired hydroxypropionic acid can be prepared by fermentation. Due to the high selectivity of the microorganisms used, fermentation conversion is usually carried out with high selectivity, high yield, and almost no by-products. In addition, side reactions can be avoided by carrying out the fermentation process at a low temperature of 30-60°C. In contrast, large-scale chemical processes in the petrochemical industry are usually carried out at much higher temperatures, typically >200°C, to optimize yields. However, high reaction temperatures always lead to the formation of side reactions and pyrolysis products.
[0038] The method just described is, for example, documented in DE 10 2006 039 203 A1, in which an acrylic acid-containing fluid is purified by suspension crystallization or layer crystallization.
[0039] There are also different methods available for producing alcohols from renewable raw materials.
[0040] For example, butanol can be obtained through the fermentation of plant biomass, which is typically pre-treated. Here, sucrose, starch, or cellulose are used as starting materials, and in some cases, genetically modified microorganisms (so-called "white biotechnology") are employed. In the so-called ABE process (ABE stands for acetone, butanol, and ethanol), the bacteria *Clostridium acetobutylicum* are used for fermentation to produce 1-butanol.
[0041] 2-Octanol can be obtained and isolated as a byproduct of the oxidation of ricinoleic acid to sebacic acid. n-Heptanol can be obtained from heptanal, which is produced during the thermal decomposition of ricinoleic acid (pyrolytic decomposition into heptanal and undecenoic acid).
[0042] Isoamyl alcohol is the main component of fusel oil, which is formed as a byproduct of yeast metabolism of amino acids during the alcoholic fermentation of sugar.
[0043] Compared to the other monomers contained herein, monomer a) lowers the glass transition temperature of the copolymer. This is advantageous because it facilitates the spread of the pressure-sensitive adhesive on the adhesive substrate. Furthermore, the substance can thus accommodate more resin, which also positively impacts adhesive properties.
[0044] According to the present invention, the monomer composition of copolymer A of the pressure-sensitive adhesive according to the present invention comprises a total of 75 to 99.5% by weight of monomer a). Preferably, the monomer composition of copolymer A of the pressure-sensitive adhesive according to the present invention comprises a total of 76 to 95% by weight of monomer a).
[0045] In another embodiment, the copolymer A of the pressure-sensitive adhesive according to the invention comprises at least 80% by weight, preferably at least 90% by weight, monomer a).
[0046] The monomer composition of copolymer A in the pressure-sensitive adhesive according to the invention includes isoamyl acrylate as monomer a). This is particularly advantageous because this monomer is able to lower the glass transition temperature of copolymer A. Furthermore, it does not introduce side-chain crystallinity, thus making a particularly large contribution to the formation of pressure-sensitive adhesive properties.
[0047] According to the present invention, the monomer composition of copolymer A of the pressure-sensitive adhesive according to the present invention optionally includes 0 to 24.5% by weight of one or more additional monomers [monomer c).
[0048] The additional monomer [monomer c)] is selected from (meth)acrylates, (meth)acrylamides, and monomers having at least one polymerizable vinyl group.
[0049] The copolymer A of the pressure-sensitive adhesive according to the present invention comprises a total of up to 24.5% by weight of monomer c). In principle, the monomer composition may include one (single) or more monomers c).
[0050] Examples of one or more other monomers [monomer c)] are ethyl acrylate, n-butyl acrylate, isobutyl acrylate, isoamyl acrylate, n-hexyl acrylate, 2-heptyl acrylate, n-heptyl acrylate, 2-ethylhexyl acrylate, 2-octyl acrylate, n-octyl acrylate, isooctyl acrylate, n-nonyl acrylate, isononyl acrylate, n-decyl acrylate, isodecyl acrylate, 2-[[(butylamino)carbonyl]oxy]ethyl acrylate, 2-cyanoethyl acrylate, 2-(2-ethoxyethoxy)ethyl acrylate, phenoxyethyl acrylate, isostearyl acrylate, docosyl acrylate, and 2-[2-(2-methoxyethoxy)ethoxy]ethyl acrylate; Isoborneol acrylate, norborneol acrylate, benzyl acrylate, 3,3,5-trimethylcyclohexyl acrylate, cyclohexyl acrylate, 4-[(6-acryloyloxy)hexyloxy]-4′-cyanobiphenyl, N-succinimide acrylate, 1-ethylcyclopentyl acrylate, N-tert-octylacrylamide, N-tert-butylacrylamide, dimethylacrylamide, diethylacrylamide, N-isopropylacrylamide, acrylamide, N-[3-(dimethylamino)propyl]acrylamide, diacetone acrylamide, N-(butoxymethyl)acrylamide, N-phenylacrylamide, N-[2-(dimethylamino)ethyl]acrylamide, N-[2-(diethylamino)ethyl]acrylamide, Methyl methacrylate, ethyl methacrylate, cyclohexyl methacrylate, benzyl methacrylate, isobornyl methacrylate, glyceryl methacrylate, 2-dimethylaminoethyl methacrylate, phenoxyethyl methacrylate, 9-anthrayl methyl methacrylate, 2-ethyl-2-adamantyl methacrylate, 2-(acetylacetoxy)ethyl methacrylate, 2-isopropyl-2-methacryloyloxyadamantane, isopropyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, furfuryl methacrylate, 2-methacryloyloxy-2-methyladamantane, 2-morpholinoethyl methacrylate, phenyl methacrylate, N-succinyl methacrylate Amino esters, 2-(tert-butylamino)ethyl methacrylate, 2-cyclohexylpropyl-2-yl methacrylate, 1-adamantyl methacrylate, 1-methylcyclopentyl methacrylate, 3-dimethylaminopropyl methacrylamide, N-tert-butylmethacrylamide, N-(methoxymethyl)methacrylamide, N,N-dimethylmethacrylamide, methacrylamide, N-phenylmethacrylamide, N,N-dimethylmethacrylamide, N-isopropylmethacrylamide, N-vinylformamide, N-vinylpyrrolidone, N-vinylcaprolactam, N-vinylcarbazole, N-vinylimidazolium, vinylmethyloxazolidinone, and N-vinyl-N-methylacetamide.
[0051] In one embodiment, the optional monomer c) is selected from alkyl (meth)acrylates, wherein the alcohol component of the alkyl (meth)acrylate has 1 to 18 C atoms, preferably 1 to 10 C atoms.
[0052] In one embodiment, the one or more monomers c) are selected from monomers with a minimum bio-based content of 25% by weight, preferably 50% by weight. Preferred examples are methyl acrylate, ethyl acrylate, butyl acrylate, isobutyl acrylate, n-heptyl acrylate, 2-octyl acrylate, benzyl acrylate, isobornyl acrylate, and dimethacrylamide.
[0053] In an alternative embodiment, the monomer composition comprises 10 to 22% by weight, preferably 15 to 20% by weight, of monomer c).
[0054] In a preferred embodiment of this alternative, the monomer composition includes n-heptyl acrylate and / or 2-octyl acrylate as monomer c).
[0055] In a particularly preferred embodiment, the monomer composition c) comprises 2-octyl acrylate.
[0056] Monomer c) – particularly compared to monomer a) – increases the glass transition temperature of copolymer A. This is advantageous because it allows the properties of the pressure-sensitive adhesive to be adapted to specific requirements by changing the weight ratio of monomers a) and c). Furthermore, it is presumed that they introduce entanglement into the copolymer. This is advantageous because it imparts greater toughness and cohesion to the pressure-sensitive adhesive.
[0057] The monomer composition of copolymer A of the pressure-sensitive adhesive according to the present invention includes 0.5 to 15% by weight of acrylic acid as monomer b).
[0058] In one embodiment, the monomer composition as monomer b) comprises up to 8% by weight, alternatively up to 7% by weight, and further alternatively up to 6% by weight.
[0059] Copolymer A is preferably manufactured by conventional free radical polymerization or controlled free radical polymerization. Copolymer A can be manufactured by copolymerizing monomers using conventional polymerization initiators and optionally modifiers, wherein polymerization is carried out in bulk, in emulsion such as in water or liquid hydrocarbons, or in solution at conventional temperatures.
[0060] Copolymer A is preferably manufactured by copolymerizing the monomers in a solvent, particularly preferably in a solvent with a boiling point range of 50 to 150°C, especially 60 to 120°C, using 0.01 to 5% by weight, especially 0.1 to 2% by weight of a polymerization initiator, each weight percentage being based on the total weight of the monomers.
[0061] In principle, all commonly used initiators are applicable. Examples of radical sources are peroxides, hydroperoxides, and azo compounds, such as benzoyl peroxide, cumene hydroperoxide, cyclohexanone peroxide, di-tert-butyl peroxide, cyclohexylsulfonylacetyl peroxide, diisopropyl percarbonate, tert-butyl peroctanoate, and benzipineol. Preferred radical initiators are 2,2′-azobis(2-methylbutyronitrile) (DuPont's Vazo® 67™) or 2,2′-azobis(2-methylpropionitrile) (2,2′-azobisisobutyronitrile; AIBN; DuPont's Vazo® 64™).
[0062] Preferred solvents for manufacturing copolymer A are alcohols, such as methanol, ethanol, n-propanol and isopropanol, n-butanol and isobutanol, especially isopropanol and / or isobutanol; hydrocarbons, such as toluene, especially gasoline with a boiling point range of 60 to 120°C; ketones, especially acetone, methyl ethyl ketone, methyl isobutyl ketone; esters, such as ethyl acetate; and mixtures of the above solvents. Particularly preferred solvents are mixtures containing 2 to 15% by weight, especially 3 to 10% by weight, of isopropanol, each weight percentage based on the solvent mixture used.
[0063] The copolymer A of the pressure-sensitive adhesive according to the invention preferably has a weight-average molecular weight Mw of 500,000 to 3,000,000 g / mol, and particularly preferably has a weight-average molecular weight Mw of 700,000 to 1,500,000 g / mol.
[0064] The copolymer A of the pressure-sensitive adhesive according to the invention preferably has a K value of 30 to 100, more preferably 40 to 90, and most preferably 50 to 80 according to Fickentscher.
[0065] In principle, the pressure-sensitive adhesive according to the invention may include one (single) or more copolymers A of the above types; preferably it includes exactly one such copolymer A.
[0066] Preferably, the pressure-sensitive adhesive according to the invention comprises at least 50% by weight, preferably at least 60% by weight, particularly preferably at least 65% by weight, of copolymer A, based on the total weight of the pressure-sensitive adhesive.
[0067] Preferably, the pressure-sensitive adhesive according to the invention comprises a total of 35 to 90% by weight, more preferably 40 to 75% by weight, and especially 45 to 70% by weight of the copolymer A as described above, each weight percentage being based on the total weight of the pressure-sensitive adhesive. Particularly preferably, the pressure-sensitive adhesive according to the invention comprises 35 to 90% by weight, more preferably 40 to 75% by weight, and especially 45 to 70% by weight of (exactly) one copolymer A as described above, each weight percentage being based on the total weight of the pressure-sensitive adhesive.
[0068] The pressure-sensitive adhesive according to the present invention includes one or more crosslinking agents.
[0069] The copolymer A or multiple copolymers A of the pressure-sensitive adhesive according to the invention are preferably chemically crosslinked, especially thermally crosslinked. "Thermal crosslinking" here refers to crosslinking by means of a substance capable of initiating and / or promoting a crosslinking reaction under the action of heat. Preferred thermal crosslinking agents are covalently reactive crosslinking agents, especially epoxides, isocyanates, and / or aziridines; and coordination crosslinking agents, particularly metal chelates, especially aluminum, titanium, zirconium, zinc, and / or iron chelates. Combinations of different crosslinking agents may also be used, for example, combinations of one or more epoxides with one or more metal chelates.
[0070] The pressure-sensitive adhesive according to the present invention comprises at least one coordination crosslinking agent and / or at least one covalent crosslinking agent.
[0071] Preferably, the pressure-sensitive adhesive according to the present invention comprises a covalent crosslinking agent.
[0072] In a preferred embodiment of the invention, glycidylamine is used as the covalent crosslinking agent. As particularly preferred representatives according to the invention, examples include N,N,N′,N′-tetra(2,3-epoxypropyl)cyclohexane-1,3-dimethylamine and N,N,N′,N′-tetra(2,3-epoxypropyl)-m-xylene-α,α′-diamine.
[0073] Multifunctional epoxides, especially cyclohexyl epoxides, can also be advantageously used as covalent crosslinking agents. 2,2-bis(hydroxymethyl)-1,3-propanediol or (3,4-epoxycyclohexane)methyl-3,4-epoxycyclohexyl epoxides are particularly exemplarily mentioned here.
[0074] Furthermore, polyfunctional aziridines can be used according to the present invention. For example, trimethylolpropane tris(2-methyl-1-aziridine propionate) may be mentioned.
[0075] In another preferred embodiment of the invention, isocyanates are used as covalent crosslinking agents, particularly polyfunctional isocyanate compounds. For example, toluene diisocyanate (TDI), 2,4-toluene diisocyanate dimer, 1,5-naphthalene diisocyanate (NDI), o-toluene diisocyanate (TODI), diphenylmethane diisocyanate (MDI), triphenylmethane triisocyanate, tris(p-phenyl isocyanate)thiophosphite, and polymethylene polyphenyl isocyanate can be used as polyfunctional isocyanate compounds. They can be used alone or in combination of two or more of them.
[0076] It is preferred to use at least one covalent crosslinking agent, but two or more covalent crosslinking agents may also be used, for example, by combining the two diamine compounds mentioned above.
[0077] As the coordination crosslinking agent of the present invention, chelating compounds, especially multivalent metal chelating compounds, are particularly considered. The term "multivalent metal chelating compound" should be understood as a compound in which a multivalent metal is coordinated with one or more organic compounds. As the multivalent metal atom, Al(III), Zr(IV), Co(II), Cu(I), Cu(II), Fe(II), Fe(III), Ni(II), V(II), V(III), V(IV), V(V), Zn(II), In(III), Ca(II), Mg(II), Mn(II), Y(III), Ce(II), Ce(IV), St(II), Ba(II), Mo(II), Mo(IV), Mo(VI), La(III), Sn(II), Sn(IV), Ti(IV), etc. are used. Among them, Al(III), Fe(III), Zn(II), Zr(IV), and Ti(IV) are preferred, and Fe(III) and Al(III) are particularly preferred.
[0078] In principle, all known ligands can be used as ligands for coordination crosslinking agents. However, the atoms used for coordination bonding in organic compounds can be atoms with free electron pairs, such as oxygen, sulfur, and nitrogen atoms. Examples of organic compounds that can be used include alkyl esters, alcohols, carboxylic acids, ethers, and ketones. Examples specifically listed are iron(III) acetylacetone (Fe chelate); titanium chelates, such as dipropoxybis(acetylacetone)titanium, dibutoxybis(octanediol)titanium, dipropoxybis(ethyl acetoacetate)titanium, dipropoxybis(lactic acid)titanium, dipropoxybis(triethanolamine)titanium, di-n-butoxybis(triethanolamine)titanium, tri-n-butoxy monostearate titanium, tetrabutyl titanate dimer, poly(acetylacetone titanium), etc.; aluminum chelates, such as aluminum diisopropoxy monoethyl acetate, aluminum di-n-butoxy monomethyl acetoacetate, aluminum diisobutoxy monomethyl acetoacetate, aluminum di-n-butoxy monoethyl acetoacetate, aluminum di-sec-butoxy monoethyl acetoacetate, aluminum triacetylacetone, aluminum triethyl acetoacetate, aluminum monoacetylacetone bis(ethylacetylacetone), etc.; and zirconium chelates, such as zirconium tetraacetylacetone, etc. Among these, aluminum triacetylacetone (Al chelate) and aluminum dipropoxy are preferred. They can be used individually or in combination of two or more of them.
[0079] The covalent crosslinking agent is preferably used in an amount of 0.02 to 0.5 parts by weight, preferably 0.04 to 0.3 parts by weight, based on 100 parts by weight of all copolymer A.
[0080] The coordination crosslinking agent is preferably used in an amount of 0.05 to 0.50 parts by weight, more preferably 0.1 to 0.3 parts by weight, based on 100 parts by weight of all copolymer A.
[0081] In one embodiment, a covalent crosslinking agent and a coordination crosslinking agent are used, preferably in the amounts described above.
[0082] According to this disclosure, an adhesive-enhancing resin (meaning the same as "adhesive resin") is, as commonly understood by those skilled in the art, an oligomeric or polymeric resin that improves the self-adhesiveness (tackiness, self-adhesiveness) of a pressure-sensitive adhesive compared to a pressure-sensitive adhesive that is otherwise identical but does not contain an adhesive-enhancing resin. Furthermore, the adhesive-enhancing resin can advantageously improve the wetting properties of the pressure-sensitive adhesive relative to the substrate to be bonded, its flow behavior, and / or its adhesion.
[0083] The pressure-sensitive adhesive according to the invention may further include at least one adhesive-enhancing resin. As is generally understood by those skilled in the art, this refers to an oligomeric or polymeric resin that improves the self-adhesiveness (tackiness, self-adhesiveness) of the pressure-sensitive adhesive compared to a pressure-sensitive adhesive that is otherwise identical but does not contain an adhesive-enhancing resin. Furthermore, the adhesive-enhancing resin can advantageously improve the wetting properties of the pressure-sensitive adhesive relative to the substrate to be bonded, its flow behavior, and / or its adhesion.
[0084] In principle, the one or more adhesive strength enhancing resins may be any adhesive resin compatible with pressure-sensitive adhesives, especially copolymers A or multiple copolymers A of pressure-sensitive adhesives.
[0085] In principle, at least one adhesive strength-enhancing resin in the pressure-sensitive adhesive according to the present invention can be any adhesive resin compatible with the pressure-sensitive adhesive, especially copolymers or multiple copolymers of the pressure-sensitive adhesive. In one embodiment, the adhesive strength-enhancing resin is selected from aliphatic, aromatic, and alkyl aromatic hydrocarbon resins; hydrocarbon resins based on pure monomers; hydrogenated hydrocarbon resins; functionalized hydrocarbon resins and optionally derivatized natural resins; preferably, the adhesive resin is selected from pinene resins, indene resins, and rosin resins and their disproportionated, hydrogenated, polymerized, esterified derivatives and salts; aliphatic and aromatic hydrocarbon resins; terpene resins and terpene phenol resins; and C5, C9, and other hydrocarbon resins. In principle, the pressure-sensitive adhesive according to the present invention may include one (single) or multiple adhesive strength-enhancing resins.
[0086] Preferably, the at least one adhesive-enhancing resin is selected from acrylate resins, rosin resins, and polyterpene-based resins. These resins are at least 30% by weight based on renewable raw materials.
[0087] Particularly preferably, the at least one adhesive-enhancing resin is selected from rosin resins and polyterpene-based resins. These resins are advantageous to use because a large proportion, especially all of them, can be manufactured or obtained from renewable raw materials.
[0088] In particular, the adhesive strength enhancing resin is selected from rosin resin and polyterpene phenol resin. These adhesive resins can be manufactured from renewable raw materials and have proven to be particularly suitable for improving the adhesive performance of the pressure-sensitive adhesives according to the invention to a particularly large extent.
[0089] "Rosin resin" should be understood as a group of resins, including its disproportionated, hydrogenated, polymerized, modified derivatives and salts.
[0090] Modified derivatives of rosin resins include esterified derivatives and / or further substituted derivatives, such as maleated resins (CAS: 68038-41-5).
[0091] Rosin resins are advantageous because a large proportion, and especially all, of them can be manufactured or obtained from renewable raw materials. These adhesive resins can be manufactured from renewable raw materials and have proven particularly suitable for improving the adhesive properties of pressure-sensitive adhesives according to the invention to a particularly large extent.
[0092] Most particularly preferably, the adhesive-enhancing resin is a fully hydrogenated rosin resin. This is particularly advantageous because these resins have a relatively low softening temperature, thus advantageously contributing to the formation of pressure-sensitive adhesive properties. Furthermore, they exhibit particularly good aging stability.
[0093] Preferably, the pressure-sensitive adhesive according to the invention comprises a total of 5 to 50% by weight, more preferably 7 to 45% by weight, especially 9 to 35% by weight, and most particularly preferably 10 to 32% by weight of one or more adhesive strength-enhancing resins, each weight percentage being based on the total weight of the pressure-sensitive adhesive.
[0094] In one embodiment, the pressure-sensitive adhesive according to the invention is non-foamed and comprises a total of 20 to 40% by weight, preferably a total of 25 to 35% by weight, of one or more adhesive strength-enhancing resins.
[0095] In a preferred embodiment, the pressure-sensitive adhesive according to the invention is a foam (in accordance with this disclosure, it has the same meaning as a foamed pressure-sensitive adhesive) and comprises a total of 10 to 22% by weight, preferably a total of 12 to 20% by weight, of one or more adhesive strength-enhancing resins.
[0096] Preferably, the pressure-sensitive adhesive according to the invention comprises one or more adhesive-enhancing resins having a softening temperature of 60 to 150°C, preferably 70 to 130°C, wherein the softening temperature is determined by the ring-ball method according to ASTM E28-18 (the standard was published on July 1, 2018).
[0097] The pressure-sensitive adhesive according to the invention may also include other components, such as plasticizers; fillers, especially fibers, carbon black, zinc oxide, titanium dioxide, spinel, dyes, pigments, chalk, solid or hollow glass spheres, microspheres made of other materials, such as polymeric microhollow spheres, silica and / or silicates; nucleating agents; foaming agents; compounding agents; stabilizers and / or anti-aging agents, such as primary antioxidants and / or secondary antioxidants and / or light stabilizers.
[0098] The adhesive layer may optionally be foamed, thereby leading to an advantageous further development of the invention. However, in other advantageous embodiments of the invention, the adhesive is present in an unfoamed form. Whether or not foaming is performed depends, for example, on the intended application of the adhesive. For instance, foamed adhesives can improve impact absorption, enabling the adhesive to absorb or dissipate impact energy within the adhesive film.
[0099] Foaming can be carried out by any chemical and / or physical method. However, it is preferred to obtain the foamed pressure-sensitive adhesive according to the invention by introducing microspheres and subsequently inflating them. "Microspheres" should be understood as elastic, and therefore expandable, microhollow spheres having a thermoplastic polymer shell. The spheres are filled with a low-boiling-point liquid or liquefied gas. Polyacrylonitrile, PVDC, PVC, or polyacrylate are particularly used as shell materials. As low-boiling-point liquids, hydrocarbons such as isobutane or isopentane are particularly suitable, which are liquefied gases sealed within the polymer shell under pressure.
[0100] By applying force to the microcapsules, especially through thermal action, the outer polymer shell softens. Simultaneously, the liquid foaming gas inside the shell transforms into a gaseous state. The microcapsules thus irreversibly expand and undergo three-dimensional expansion. Expansion ends when the internal and external pressures reach equilibrium. Because the polymer shell is retained, a closed-cell foam is thus obtained.
[0101] Several types of microspheres are commercially available, differing primarily in size (6 to 45 µm diameter in the unexpanded state) and the initial temperature required for expansion (75 to 220 °C). An example of a commercially available microsphere is Akzo Nobel's Expancel® DU type (DU = dry unexpanded). Unexpanded microspheres are also available in aqueous dispersions with a solids content or microsphere content of approximately 40 to 45% by weight, and in polymer-bonded microspheres (masterbatch), for example, with a microsphere concentration of approximately 65% by weight in ethyl vinyl acetate. Like the DU type, both the microsphere dispersion and the masterbatch are suitable for manufacturing foamed pressure-sensitive adhesives according to the invention.
[0102] The foamed pressure-sensitive adhesive according to the invention can also be manufactured using so-called pre-expanded microspheres. In this group, expansion occurs before incorporation into the polymer matrix. Pre-expanded microspheres are commercially available, for example, under the name Dualite® or model DE (Dry Expanded).
[0103] For the foamed adhesive layer, the density of the adhesive film is preferably between 200 kg / m³ and 1000 kg / m³, more preferably between 500 kg / m³ and 980 kg / m³, and very preferably between 700 kg / m³ and 950 kg / m³.
[0104] Preferably, the poly(meth)acrylate is crosslinked using a crosslinking agent-accelerator system.
[0105] A particularly preferred crosslinker-accelerator system comprises at least one epoxy-containing substance as a crosslinker and at least one substance as an accelerator that promotes the linking reaction at a temperature below the melting temperature of poly(meth)acrylate. This system requires the polymer to contain functional groups capable of crosslinking with epoxy groups. Suitable epoxy-containing substances are polyfunctional epoxides, especially difunctional or trifunctional epoxides (i.e., epoxides having two or three epoxy groups), and also suitable are epoxides with higher functionality or mixtures of epoxides with different functionalities. As an accelerator, amines (formally considered as substituted products of ammonia), such as primary and / or secondary amines; especially tertiary and / or polyfunctional amines, are preferred. Substances having multiple amino groups can also be used, wherein these amino groups can be primary and / or secondary and / or tertiary amino groups, especially diamines, triamines, and / or tetraamines. Amines that do not react or only react slightly with the polymer constituent units are particularly preferred. Phosphorus-based accelerators, such as phosphine and / or phosphonium compounds, can also be used.
[0106] As functional groups for the poly(meth)acrylate to be crosslinked, acid groups (e.g., carboxylic acid groups, sulfonic acid groups, and / or phosphonic acid groups) and / or hydroxyl and / or anhydride groups and / or epoxy and / or amino groups are particularly suitable. Particularly preferred is that the polymer contains acrylic acid and / or methacrylic acid introduced during polymerization.
[0107] However, it may also be advantageous not to use an accelerator, as accelerators may, for example, tend to cause yellowing (especially nitrogen-containing substances). As a crosslinking agent that does not require the addition of an accelerator, epoxycyclohexyl derivatives are suitable, especially when carboxylic acid groups are present in the poly(meth)acrylate to be crosslinked. This can be achieved, for example, by introducing at least 5% by weight of acrylic acid into the polymer through polymerization. In the polymer to be crosslinked, it is advantageous, in particular, the absence of proton acceptors, electron pair donors (Lewis bases), and / or electron pair acceptors (Lewis acids). The absence of these substances particularly relates to externally added accelerators, i.e., those not introduced into or incorporated into the polymer backbone through polymerization; but it is particularly preferred that neither externally added accelerators nor polymerization-introduced accelerators are present, especially the complete absence of accelerators. Particularly preferably, the crosslinking agent is epoxycyclohexylcarboxylate, especially (3,4-epoxycyclohexane)methyl-3,4-epoxycyclohexylcarboxylate (Uvacure® 1500).
[0108] In one embodiment, the pressure-sensitive adhesive according to the invention comprises another polymer, preferably rubber, particularly natural rubber or synthetic rubber.
[0109] Natural rubber is an elastic polymer traceable to plant products, particularly latex. It is a key raw material used in the processing of natural rubber adhesives. Natural rubber is an elastomer that, due to its natural origin, contains other byproducts such as proteins. Natural rubber itself does not exhibit pressure-sensitive adhesive properties. To impart these properties, adhesive resins are added, typically rosin-based or hydrocarbon-based resins. Additionally, natural rubber-based adhesives often contain anti-aging agents to protect the double bonds present in natural rubber from oxidative degradation. Besides the aforementioned formulation components, fillers are frequently added to natural rubber formulations.
[0110] The synthetic rubber is preferably acrylonitrile-butadiene rubber or rubber containing AB, ABA, or (AB). n (AB) n X or (ABA) n X-structured block copolymers
[0111] in
[0112] - Block A represents, independently of each other, a polymer formed by polymerizing at least one vinyl aromatic compound;
[0113] - Block B independently represents a polymer formed by polymerizing a conjugated diene and / or isobutylene having 4 to 18 C atoms, or a partially or fully hydrogenated derivative of such polymer;
[0114] - X represents a residue of the coupling agent or initiator; and
[0115] - n represents an integer greater than or equal to 2.
[0116] In particular, if the pressure-sensitive adhesive according to the invention comprises multiple synthetic rubbers, then all synthetic rubbers are independently acrylonitrile-butadiene rubbers or block copolymers having the structure described above. Therefore, the pressure-sensitive adhesive according to the invention may also comprise a mixture of different synthetic rubbers having the structure described above.
[0117] Therefore, a suitable block copolymer (vinyl aromatic block copolymer) preferably comprises one or more rubbery blocks B (soft blocks) and one or more glassy blocks A (hard blocks). Particularly preferably, at least one synthetic rubber is a block copolymer having an AB, ABA, (AB)2X, (AB)3X, or (AB)4X structure, wherein A, B, and X have the aforementioned meanings. In particular, the pressure-sensitive adhesive comprises a mixture of various block copolymers having an AB, ABA, (AB)2X, (AB)3X, or (AB)4X structure, preferably comprising at least a diblock copolymer AB, a triblock copolymer ABA, and / or a triblock copolymer (AB)2X.
[0118] Block A is typically a glassy block, preferably with a glass transition temperature (Tg, DSC) above room temperature. Particularly preferably, the glassy block has a Tg of at least 40°C, especially at least 60°C, most particularly preferably at least 80°C, and extremely preferably at least 100°C. The proportion of vinyl aromatic block A in the total block copolymer is preferably 10 to 40% by weight, particularly preferably 20 to 33% by weight. The vinyl aromatic compound used to constitute block A preferably includes styrene and its derivatives, especially styrene and α-methylstyrene. Therefore, block A can exist as a homopolymer or copolymer. Particularly preferably, block A is polystyrene.
[0119] The vinyl aromatic block copolymer also typically has rubbery block B or soft block, which preferably has a Tg below room temperature. The Tg of the soft block is particularly preferably less than 0°C, especially less than -10°C, for example less than -40°C, and most particularly preferably less than -60°C.
[0120] Preferred conjugated dienes for the monomers used in the soft block B are particularly selected from butadiene, isoprene, ethylbutadiene, phenylbutadiene, isoprene, pentadiene, hexadiene, ethylhexadiene, dimethylbutadiene, and farnesene isomers, as well as any mixtures of these monomers. Block B may also exist as a homopolymer or copolymer.
[0121] Particularly preferably, the conjugated diene used as the monomer of the soft block B is selected from butadiene and isoprene. For example, the soft block B is polyisoprene, polybutadiene, or a partially or fully hydrogenated derivative of one of these polymers, such as, in particular, polybutenebutadiene; or a polymer formed from a mixture of butadiene and isoprene. Most particularly preferably, block B is polybutadiene.
[0122] In one embodiment, the pressure-sensitive adhesive according to the invention comprises a blend of at least one copolymer A and at least one rubber, preferably a synthetic rubber, particularly according to the above description of these polymers.
[0123] In one embodiment, the pressure-sensitive adhesive according to the invention comprises a blend of at least one copolymer A and at least one rubber, preferably a synthetic rubber, in total 10 to 40% by weight.
[0124] The pressure-sensitive adhesive according to the present invention is preferably manufactured by solution, that is, by dispersing or dissolving the components in a suitable solvent and mixing them; after the mixing process is completed, the solvent is removed by conventional methods.
[0125] The pressure-sensitive adhesive according to the invention can be used as is, for example, in the form of a layer or in the form of a carrier-free layer of the pressure-sensitive adhesive according to the invention, also referred to as a "transfer tape". This transfer tape is preferably applied only to a material that temporarily protects the adhesive surface, makes the pressure-sensitive adhesive easier to handle, and makes it easier to apply. This material is also called a release liner, or simply a "liner," and is generally easy to remove again, especially with a suitable surface coating. A liner may also be provided on the second side of the transfer tape.
[0126] The release liner is, in particular, a carrier material having an anti-sticking feature (coating or treatment) on one or preferably both sides. Various types of paper can be considered as carrier materials for the release liner, optionally in combination with a stabilizing extrusion coating. Other suitable liner carrier materials are films (or foils), especially polyolefin films, such as films based on ethylene, propylene, butene, and / or hexene. Preferred carrier materials are paper, such as glassine paper. Paper is preferred, especially because the concept of obtaining the components from renewable raw materials can thus also be extended to auxiliary materials for adhesive tapes.
[0127] Silicone systems are frequently used as anti-stick release coatings. Commonly used pads include, for example, silicone paper and silicone film.
[0128] In order to bond the transfer tape to the surface of the substrate, the pads or multiple pads are then removed, so that each of the two adhesive sides obtains direct contact with the substrate surfaces to be bonded to each other. Therefore, the pads are not product components, and accordingly are not included in the tape, but are merely aids for handling the tape.
[0129] Preferably, the pressure-sensitive adhesive according to the invention is used in the structure of multilayer tapes or in the manufacture of multilayer tapes. The corresponding multilayer tapes typically include at least one carrier layer and may have an outer layer of the pressure-sensitive adhesive according to the invention on one or both sides. In tapes with adhesive settings on both sides, one or both outer layers may be the pressure-sensitive adhesive according to the invention. In the latter case, the pressure-sensitive adhesive layers may differ in their chemical composition and / or their chemical and / or physical properties and / or their geometry (e.g., layer thickness), but particularly preferably, they are identical in their chemical composition and / or their chemical and / or physical properties. For multilayer tapes, one or two outer pressure-sensitive adhesive layers may also be covered with a pad.
[0130] The tape may have other layers, such as other carrier layers or functional layers.
[0131] As the carrier material for multilayer adhesive tapes, bio-based materials are preferred, such as those selected from the following list: paper; bio-based fabrics or nonwovens, such as fabrics or nonwovens made of cotton or viscose; celluloid; cellulose acetate; bio-based polyethylene (PE) and polypropylene (PP) films; films made of thermoplastic starch; and bio-based polyester films, such as polylactide (PLA; polylactic acid), polyethylene terephthalate (PET), polyethylene furanate (PEF), or polyhydroxyalkanoate (PHA) films. Particularly preferred is the carrier material being a PET film. PET film is preferred, for example, because it can be used as a recyclable material, thus taking sustainability into consideration in this way.
[0132] In this disclosure, the term "bio-based content" describes the weight percentage of a monomer, composition (e.g., copolymer component A), or substance (e.g., pressure-sensitive adhesive) that is entirely based on renewable raw materials. The minimum bio-based content therefore describes a lower limit for the bio-based content of a monomer, composition, or substance.
[0133] Similarly, when, for example, alcohols are manufactured in a bio-based manner, but acid groups are based on petrochemical processes or partially bio-based processes, such as through a (bio)mass balance scheme, the monomer has a certain minimum bio-based content. Therefore, in the above example, the bio-based proportion of alcohols is used as the lower limit of the bio-based content, i.e., the minimum bio-based content (excluding the proportion of acid groups produced or possibly produced by a (bio)mass balance scheme).
[0134] In one embodiment, the pressure-sensitive adhesive is characterized in that at least 50% by weight, preferably at least 60% by weight, and particularly preferably greater than 70% by weight of the monomers used to manufacture copolymer component A are entirely based on renewable raw materials. As previously stated, the definition of "entirely based on renewable raw materials" also includes a certain weight percentage of the monomers being entirely based on renewable raw materials, but does not necessarily require that all of a monomer be entirely based on renewable raw materials (e.g., 2-octyl acrylate, which, for example, has 40% by weight entirely based on renewable raw materials).
[0135] In one embodiment, the pressure-sensitive adhesive is characterized in that at least 50% by weight, preferably at least 60% by weight, and particularly preferably more than 70% by weight, is based on renewable raw materials.
[0136] Unlike petrochemical-based products, those (bio-based products) that have a large proportion, preferably all traceable to renewable raw materials, have a naturally occurring proportion of radioactive carbon atoms (¹). 4 (C isotopes). The proportions of these isotopes can be determined, and the amount of natural raw materials used can be inferred from them. Here, according to ASTM D6866-04,¹ 4 The proportion of renewable feedstocks is determined using the C1 radiocarbon dating method. This method is based on the measurement of isotopes¹ 4 C, the isotope is present in carbon in nature (i.e., biomass) at a concentration of 10. - ¹ 0 It exists at an abundance of %. A half-life of 5730 years is long enough that, within the typical lifespan of adhesive products such as pressure-sensitive tapes,¹ 4 The carbon content does not change significantly due to decay (but is short enough that historical artifacts made from biological materials can be dated). Isotope¹ 4 C is measured by liquid scintillation spectroscopy or mass spectrometry. Due to the aforementioned half-life, it is undetectable within the detection limit in carbon samples older than 60,000 years.¹ 4 C isotopes. Therefore, the carbon in petroleum-based feedstocks, which are millions of years old, used in the petrochemical industry no longer contains¹ carbon. 4 C isotopes. The same applies to feedstocks based on natural gas and coal.
[0137] Therefore, another subject of the invention is an adhesive tape comprising a carrier material and comprising, at least on one of its two outer sides, preferably on both outer sides, a pressure-sensitive adhesive according to the invention. Preferably, the carrier material is a PET film. The PET film preferably has a thickness of 1 to 5 µm; the layer or plurality of layers of the pressure-sensitive adhesive according to the invention preferably each have a layer thickness of 20 to 30 µm. Therefore, the preferred total thickness of the tape according to the invention is 41 to 65 µm. In a preferred embodiment, a PET film made from recycled materials is used as the carrier material.
[0138] To anchor the pressure-sensitive adhesive to a carrier or other substrate, it is advantageous to treat the substance and / or substrate with corona or plasma prior to coating. Furthermore, to anchor the pressure-sensitive adhesive layer to other layers, particularly to a carrier layer, it is advantageous to perform chemical anchoring, for example, via a primer.
[0139] Another subject of the present invention is the use of the pressure-sensitive adhesive or tape according to the invention for adhesive bonding in the manufacture of electronic, optical and / or precision mechanical equipment.
[0140] Electronic, optical, and precision mechanical equipment for the purposes of this application, particularly those equipment classified in Class 9 of the 10th edition of the International Classification of Goods and Services for the Purposes of the Registration of Marks (Nice Classification) (NCL(10-2013)), provided that they are electronic, optical, or precision mechanical equipment; also includes clocks and watches and timekeeping instruments under Class 14 (NCL(10-2013)), for example, especially
[0141] Scientific, nautical, surveying, photography, cinematography, optics, weighing, measurement, signaling, control, rescue, and teaching devices and instruments;
[0142] Devices and instruments used for conducting, switching, converting, storing, regulating and controlling electricity;
[0143] Image recording, processing, transmission, and reproduction devices, such as television sets;
[0144] Sound recording, processing, transmission, and reproduction equipment, such as broadcasting equipment;
[0145] Computers, computing devices and data processing equipment, mathematical equipment and instruments, computer accessories; office equipment, such as printers, fax machines, copiers, typewriters; and data storage devices;
[0146] Remote communication equipment and multifunctional devices with remote communication capabilities, such as telephones and answering machines;
[0147] Chemical and physical measuring equipment, control equipment and instruments, such as battery chargers, multimeters, lamps, and tachometers;
[0148] Nautical equipment and instruments;
[0149] Optical equipment and instruments;
[0150] Medical equipment and instruments, as well as equipment and instruments for athletes;
[0151] Clocks and precision timepieces;
[0152] Solar cell modules, such as electrochemical dye solar cells, organic solar cells, and thin-film batteries; and
[0153] Fire extinguishing equipment.
[0154] Currently, technological development in the electronics field often focuses on designing devices that are increasingly smaller and lighter so that their owners can carry them at any time. This is typically achieved by realizing low weight and / or appropriate size for such devices. These devices are also known as mobile devices or portable devices. In this context, precision mechanical and optical devices are also increasingly incorporating electronic components, thereby increasing the possibility of miniaturization. As mobile devices are carried, they are increasingly subjected to mechanical loads, such as impacts to edges, drops, contact with other hard objects in a bag, and even continuous movement simply due to carrying. Compared to "non-mobile" devices that are typically installed indoors and do not move or move very little, mobile devices also bear stronger loads due to moisture, temperature effects, etc. The pressure-sensitive adhesive according to the invention has proven to be particularly preferably able to withstand and mitigate or compensate for such disturbances. Therefore, the pressure-sensitive adhesive according to the invention or the tape according to the invention is preferably used for adhesive connections in the manufacture of portable electronic devices.
[0155] Portable electronic devices include, for example:
[0156] Cameras, digital cameras; photographic accessories such as exposure meters, flash units, apertures, camera housings, lenses; cinema cameras, video cameras;
[0157] Small computers (mobile computers, pocket computers, calculators), laptops, notebooks, netbooks, ultrabooks, tablets, handheld devices, electronic calendars and organizers (so-called "Electronic Organizers" or "Personal Digital Assistants", PDAs, Palmtops), modems;
[0158] Operating units of computer accessories and electronic devices, such as mice, drawing tablets, graphics tablets, microphones, speakers, game consoles, game controllers, remote controls, remote controllers, and touchpads.
[0159] Monitors, displays, screens, touchscreens (sensor screens, "touchscreen devices"), projectors;
[0160] E-book readers;
[0161] Small television sets, pocket television sets, movie playback devices, video playback devices;
[0162] Radios (including small and pocket broadcasting devices), Walkmen, Discmen, music playback devices for CDs, DVDs, Blu-rays, cassette tapes, USB, MP3s, etc.; headphones;
[0163] Cordless phones, mobile phones, smartphones, walkie-talkies, hands-free devices, personal paging devices (Pager, Pieper);
[0164] Portable defibrillators, blood glucose measuring devices, blood pressure measuring devices, pedometers, and pulse measuring devices;
[0165] Flashlight, laser pointer;
[0166] Mobile detectors, optical magnification equipment, long-range observation equipment, and night vision equipment;
[0167] GPS devices, navigation devices, and portable interface devices for satellite communication;
[0168] Data storage devices (USB flash drives, external hard drives, memory cards); and
[0169] Wristwatches, digital watches, pocket watches, chain watches, and stopwatches.
[0170] Another subject of the present invention is a method for manufacturing pressure-sensitive adhesives or tapes according to the present invention.
[0171] The pressure-sensitive adhesive or tape according to the invention is manufactured by polymerization, which may be carried out in an organic solvent; as an emulsion polymerization; in a closed sleeve; or in the form of a syrup.
[0172] In one embodiment, the polymerization of the pressure-sensitive adhesive is carried out in an organic solvent or a mixture of organic solvents.
[0173] In one embodiment, the polymerization of the pressure-sensitive adhesive takes place within a closed enclosure. The closed enclosure should be understood as any system in principle, constructed in a way that does not impede the polymerization process, spatially confining and completely surrounding the composition to be polymerized or being polymerized, and at least restricting, preferably preventing, the passage of at least air, water, and the enclosed monomers.
[0174] The material of the sealing sleeve is preferably selected from ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, polyethylene, polypropylene, polybutadiene, ionomer film, and mixtures thereof; more preferably selected from polyethylene, ethylene-vinyl acetate copolymer, and mixtures thereof. The thickness of the sealing sleeve material is preferably 30 to 100 µm, more preferably 35 to 70 µm, and especially 40 to 60 µm. The thickness of the sealing sleeve filled with the material to be polymerized is preferably 2 to 22 mm, more preferably 5 to 21 mm, and especially 7 to 20 mm. The sealing sleeve is manufactured, for example, by stacking two film webs on top of each other and heat-sealing them on the longitudinal side and the lowermost side edge. The monomer mixture is then filled using a liquid forming, filling, and sealing machine. The sealing is then performed segmentally through the liquid surface to form a plurality of filled sealing sleeves, which are then separated from each other.
[0175] In one embodiment, the polymerization of the pressure-sensitive adhesive is carried out as emulsion polymerization. For example, a description of this method can be found in "Emulsion Polymerization and Emulsion Polymers" by Peter A. Lovell and Mohamed S. El-Aasser—Wiley-VCH 1997—ISBN 0-471-96746-7 or EP 1 378 527 B1.
[0176] In emulsion polymerization, it cannot be ruled out that not all monomers will be converted into polymers. Therefore, it is obvious that the residual monomer content should be as low as possible.
[0177] Preferably, an acrylate pressure-sensitive adhesive comprising a polymer dispersion is provided, wherein the residual monomer content is less than or equal to 1% by weight, particularly less than or equal to 0.5% by weight (based on the mass of the base polymer).
[0178] In one embodiment, the polymerization of the pressure-sensitive adhesive is carried out as a syrup.
[0179] Monomer mixtures often have too low a viscosity initially to be easily handled. To increase the viscosity, the monomer mixture is prepolymerized to a syrupy consistency, which advantageously allows for conversion rates of 2-20%. This forms a syrup that can be well coated onto a carrier material. UV light with a wavelength of 280-450 nm is preferably used to initiate prepolymerization.
[0180] Furthermore, the monomer may optionally be mixed with the resin after prepolymerization or preferably before prepolymerization. Additional monomers may be added to or mixed with the syrup before complete polymerization.
[0181] The method according to the invention is particularly advantageous for manufacturing, for example, tapes, because the prepolymer can be coated onto the carrier as a syrup. Detailed Implementation
[0182] Measurement and testing methods:
[0183] Determination of the glass transition temperature (Tg) of pressure-sensitive adhesives
[0184] The static glass transition temperature of the pressure-sensitive adhesive was determined by dynamic differential calorimetry (DDK), or synonymously dynamic scanning calorimetry (DSC). For this purpose, approximately 5 mg of untreated pressure-sensitive adhesive sample was weighed into an aluminum crucible (25 µl volume) and sealed with a perforated cap. Measurements were performed using a Netzsch DSC 204 F1. For inertization, the operation was conducted under nitrogen. The sample was first cooled to -150 °C, then heated to +150 °C at a heating rate of 10 K / min, and then cooled again to -150 °C. A second heating curve was then run again at 10 K / min, and the change in heat capacity was recorded. Here, the glass transition was identified as a step in the thermogram (heat flow-temperature diagram). The glass transition temperature Tg was obtained as follows: the regions of linearity before and after the step were extended along the direction of increasing temperature (the region before the step) and the direction of decreasing temperature (the region after the step), respectively. In the stepped region, a fitted straight line parallel to the vertical axis is positioned to intersect the two extended lines, such that the two areas (located between an extended line, the fitted straight line, and the measured curve, respectively) have the same area. The intersection point of the fitted straight line and the measured curve in this configuration gives the glass transition temperature.
[0185] Determination of molecular weight
[0186] The number-average molar mass (Mn) and weight-average molar mass (Mw) data in this specification pertain to determinations known per se by gel permeation chromatography (GPC). The determination was performed on 100 µl of clarified, filtered sample (sample concentration 4 g / L). Tetrahydrofuran containing 0.1 vol% trifluoroacetic acid was used as the eluent. Measurements were performed at 25°C.
[0187] A PSS-SDV type, 5 µm, 10³ Å, 8.0 mm x 50 mm column was used as the guard column (the data here and below are, in order: type, particle size, porosity, inner diameter x length; 1 Å = 10). -10 For separation, PSS-SDV type, 5µm, 10³ Å and 10 m were used. 5 Å and 10 6The chromatographic column assembly was Å, with each column being 8.0 mm x 300 mm (Polymer Standards Service columns; measured using a Shodex RI71 differential refractometer). The flow rate was 1.0 mL per minute. Calibration was performed using a commercially available ReadyCal-Kit Poly(styrene) high from PSS Polymer Standard Service GmbH (Mainz). Data were generally converted to polymethyl methacrylate (PMMA) based on Mark-Houwink parameters K and alpha, and are presented in PMMA mass equivalents.
[0188] Determination of shear life ("SSZ 23℃; 1 kg" and "SSZ 70℃; 0.5 kg")
[0189] Shear strength was determined by shear life (“SSZ 23℃; 1 kg”) under test climatic conditions of 23 + / - 1℃ temperature and 50% + / - 5% relative humidity.
[0190] The test sample was cut to a width of 13 ± 0.2 mm and stored in the stated climate for at least 16 hours. The test used a 50 x 25 mm, 2 mm thick ASTM steel sheet with a 20 mm marking line, which was thoroughly cleaned with acetone multiple times before bonding and then air-dried for 10 minutes. The bonding area was 13 x 20 ± 0.2 mm. Using a scraper, the test strip was applied longitudinally and centered on the adhesive substrate, avoiding air entrainment, so that the upper edge of the test sample was precisely at the 20 mm marking line.
[0191] The back of the test sample was covered with aluminum foil. The free-protruding end was covered with paper. Then, the tape was rolled back and forth twice using a 2 kg roller. After rolling, a belt loop (weighing 5-7 g) was installed at the protruding end of the tape.
[0192] Next, use screws and nuts to secure the adapter plate to the front of the shear test plate. To ensure the adapter plate is firmly in place on the plate, tighten the screws by hand.
[0193] The plate thus prepared is fixed to the timer by means of a hook via an adapter plate; then a 1 kg weight is suspended into the belt loop without impact.
[0194] The dwell time between rolling and applying load was 12 minutes. The time until adhesive bond failure was measured in minutes; the result was the average of three measurements. A shear life exceeding 10,000 minutes was considered a good result.
[0195] The shear life was determined under test conditions of 70 ± 1 °C and 10% ± 10% relative humidity (“SSZ 70 °C; 0.5 kg”) in a similar manner to the method described above, wherein the prepared plate was equilibrated for 30 min under the test conditions of 70 °C before suspending the 0.5 kg weight. A shear life exceeding 10,000 min at 70 °C was considered a good result.
[0196] Adhesion on steel
[0197] Adhesive strength was determined under test climatic conditions of 23°C ± 1°C and 50% ± 5% relative humidity. Samples were cut to 20 mm wide and adhered to a steel plate (ASTM). The steel plate was cleaned and conditioned prior to measurement. To do this, the plate was first wiped with solvent and then left in the air for 5 minutes to allow the solvent to evaporate. Subsequently, a 25 µm thick etched PET film was used to cover the side of the tape facing away from the test substrate to prevent the sample from elongating during measurement. The test sample was then rolled onto the substrate. For this, a 4 kg roller was used to roll the tape back and forth five times at a rolling speed of 10 m / min. After rolling for 1 min, the plate was pushed into a special fixture. Adhesive strength was measured using a Zwick tensile testing machine; the sample was peeled at a 180° angle and a speed of 300 mm / min. The results are expressed in N / cm and are the average of five individual measurements.
[0198] K value (according to Fikentscher)
[0199] The K-value is a measure of the average molecular size of a polymer. To measure it, a 1% (1 g / 100 mL) polymer solution in toluene is prepared, and its kinematic viscosity is determined using a Vogel-Ossag viscometer. The relative viscosity is obtained after normalization to the toluene viscosity, from which the K-value can be calculated according to Fikentscher (Polymer 1967, 8, 381 ff).
[0200] Glass transition temperature Tg; glass transition frequency f; loss factor tanδ
[0201] The glass transition temperature (Tg), glass transition frequency (fg), and loss factor (tanδ) were determined by dynamic mechanical analysis (DMA); the following methods were used: the glass transition temperature was determined by temperature scanning, the glass transition frequency was determined by time-temperature superposition (TTS), and the loss factor (as well as the loss modulus and storage modulus) was determined by frequency scanning. Unless otherwise specified individually, all data within the scope of this specification refer to the results of these measurements.
[0202] DMA leverages the fact that the properties of viscoelastic materials under sinusoidal mechanical loads depend not only on the load frequency (i.e., time) but also on temperature. In the TTS method, frequency measurements taken at regular temperature intervals are converted into frequency sweeps; this allows the range achievable through measurement to be extended downwards and upwards by several orders of magnitude.
[0203] All DMA method operations:
[0204] Measuring instrument: Rheometric Scientific RDA III; Measuring head: spring-supported with normal force; Temperature control: heating chamber; Measuring geometry: parallel plate arrangement, sample thickness 1 (±0.1) mm; Sample diameter 25 mm (to prepare a 1 mm thick sample, 5 layers (200 μm each) of the tape under study were laminated together; since the PET carrier does not significantly contribute to the rheological properties, its presence can be ignored).
[0205] Temperature scan:
[0206] Measurement frequency: 10 rad / s; temperature range: -40℃ to +130℃; heating rate: 2.5℃ / min; deformation: 1%.
[0207] Frequency scan:
[0208] Measurement frequency: 0.1 to 100 (512) rad / s; temperature 25℃; stress 2500 Pa; deformation 1%.
[0209] TTS measurement:
[0210] Measurement frequency 0.1 to 512 rad / s; temperature -35 to +190°C, in 15°C increments; deformation 1%.
[0211] Table 1: Commercially available chemicals used
[0212]
[0213] Manufacturing of polyacrylates:
[0214] Polyacrylate (PI)
[0215] 50 g of acrylic acid (AA), 950 g of isoamyl acrylate (iAmA), and 724 g of gasoline / acetone (70:30) were loaded into a standard 3 L container for free radical polymerization. After purging with nitrogen for 45 minutes with stirring, the reactor was heated to 58°C and 0.5 g of Vazo® 67 was added. The jacket temperature was then set to 75°C, and the reaction was carried out at this constant external temperature. Another 0.5 g of Vazo® 67 was added after 1 h of reaction. After 3 h, the mixture was diluted with 200 g of gasoline / acetone (70:30), and after 6 h, it was diluted with 100 g of gasoline / acetone (70:30). To reduce residual initiator, 1.5 g of Perkadox® 16 was added after 5.5 h and 7 h. The reaction was terminated after 24 h of reaction time and cooled to room temperature.
[0216] Polyacrylates P-II to P-VII
[0217] Except for the monomer composition, polyacrylates II to VII (P-II to P-VII) are manufactured in the same manner as polyacrylate I (PI). The monomer composition is listed in Table 2.
[0218] Table 2: Monomer composition of copolymer A and other polyacrylates
[0219]
[0220] ¹ Based on the monomer composition of polyacrylate [monomer a) + monomer b) + monomer c) constitute 100 parts by weight of polyacrylate];
[0221] Comparative example.
[0222] Manufacturing method of pressure-sensitive adhesive:
[0223] Method – Manufacturing pressure-sensitive adhesives from solvents
[0224] The manufactured polyacrylate was then mixed with a crosslinking agent and optionally with an adhesive resin. The resulting composition was applied from solution to a silicone release film (50 µm polyester) using a doctor blade, followed by drying (coating speed 2.5 m / min, drying channel 15 m, temperatures: zone 1: 40 °C, zone 2: 70 °C, zone 3: 95 °C, zone 4: 105 °C). The coating weight of the dried material was 50 g / m².
[0225] Table 3: Composition of pressure-sensitive adhesives; film thickness and measurement results
[0226]
[0227] The weight percentages shown are based on the composition of the pressure-sensitive adhesive (100 parts by weight consisting of polyacrylate + optional pressure-sensitive adhesive);
[0228] ³ A crosslinking agent (data based on 100 parts by weight of polyacrylate) is added as an additive to 100 parts by weight of pressure-sensitive adhesive (polyacrylate + optional pressure-sensitive adhesive constitute 100 parts by weight);
[0229] Comparative example.
Claims
1. A pressure-sensitive adhesive, comprising: - At least one copolymer A, traceable to a monomer composition comprising: a) Isoamyl acrylate, greater than 75% to 99.5% by weight, b) 0.5 to 15% by weight of acrylic acid; and optionally c) 0 to 24.5% by weight of one or more other monomers; as well as - One or more cross-linking agents.
2. The pressure-sensitive adhesive according to claim 1, characterized in that, The pressure-sensitive adhesive includes one or more adhesive-enhancing resins.
3. The pressure-sensitive adhesive according to claim 2, characterized in that, The adhesive-enhancing resin is based on at least 30% by weight of renewable raw materials.
4. The pressure-sensitive adhesive according to any one of the preceding claims, characterized in that, The crosslinking agent is a covalent crosslinking agent.
5. The pressure-sensitive adhesive according to any one of the preceding claims, characterized in that, The monomer composition comprises a total of 76 to 95% by weight of monomer a).
6. The pressure-sensitive adhesive according to any one of the preceding claims, characterized in that, The monomer composition includes at least 80% by weight, preferably at least 90% by weight, of monomer a).
7. The pressure-sensitive adhesive according to any one of the preceding claims, characterized in that, The monomer composition includes up to 24.5% by weight of monomer c), wherein one or more monomers c) are selected from (meth)acrylates, (meth)acrylamides and monomers having at least one polymerizable vinyl group.
8. The pressure-sensitive adhesive according to any one of the preceding claims, characterized in that, The one or more monomers c) are selected from alkyl (meth)acrylates, wherein the alcohol component of the alkyl (meth)acrylate has 1 to 18 C atoms, preferably 1 to 10 C atoms.
9. The pressure-sensitive adhesive according to any one of the preceding claims, characterized in that, The monomer composition includes 10 to 22% by weight, preferably 15 to 20% by weight of monomer c).
10. The pressure-sensitive adhesive according to any one of the preceding claims, characterized in that, The one or more monomers c) are selected from methyl acrylate, ethyl acrylate, butyl acrylate, isobutyl acrylate, n-heptyl acrylate, 2-octyl acrylate, benzyl acrylate, isobornyl acrylate, and dimethylacrylamide.
11. The pressure-sensitive adhesive according to any one of the preceding claims, characterized in that, At least 40% by weight, preferably at least 50% by weight, and particularly preferably more than 60% by weight, of the monomers used to manufacture copolymer component A are entirely based on renewable raw materials.
12. The pressure-sensitive adhesive according to any one of the preceding claims, comprising at least 50% by weight, preferably at least 60% by weight, particularly preferably at least 65% by weight, of copolymer A, based on the total weight of the pressure-sensitive adhesive.
13. A tape comprising the pressure-sensitive adhesive according to any one of claims 1 to 12.
14. Use of the pressure-sensitive adhesive according to any one of claims 1 to 12 or the tape according to claim 13 for the manufacture of adhesive joints in electronic, optical and / or precision mechanical equipment.
Citation Information
Patent Citations
Process for the production of acrylic acid purified by crystallization from hydroxypropionic acid and apparatus therefor
DE102006039203A1
Pressure sensitive adhesifs for flexible PVC support
EP1378527B1
Aqueous pressure-sensitive adhesive composition and utilization thereof
EP2062955A1
Use of a 2-octyl acrylate polymer as a binding agent in a coating composition
EP3013767A1
Pressure-sensitive adhesive composition
EP4196509A1